Physical and mechanical properties of fibreboards from oil palm fibres and polyethylene / Mohd Ariff Jamaludin ... [et al.] - Jamaludin, Mohd Ariff; Razali Bujang, Yul Haidzir; Ramli, Ridzuan; Nordin, Kamarulzaman; Ahmad, Mansur (Faculty of Applied Sciences, 2005)
Three different oil palm based fibreboards were used in this study, each using different types of fibres. The fibre types were frond (OPF), trunk (OPT) and empty fruit bunch (EFB). Four different plastics mixes of 0%, 5%, 12% and 20% was used for each of the fibreboard types. There were a total of twelve fibreboard types (3 fibres types X 4 polyethylene percentage content) used in this study. The fibreboards were manufactured to a targeted density of 850 kg/m3. Urea formaldehyde (UF) adhesive was used as part of the matrix at resin level of 10 percent. All the OPF boards and hybrid boards with 5% and 12% plastic content irrespective of the fibre types satisfied the 200-type board for modulus of rupture (MOR) as stated in the JIS-A-5906. The OPT boards and hybrid boards with 20% plastic content passed the JIS-A-5906 150-type board. The EFB boards only passed the JIS-A-5906 type-50 for the MOR. For Internal bonding (IB), all the fibreboards were able to meet the requirements of JIS-A-5906 type-300 board. In the case of thickness swelling (TS), all the fibreboards failed to meet the requirement as specified in the JIS-A-5906 standard. However, the dimensional stability of the fibreboards increases with increase quantity of plastic used.